1964
DOI: 10.1073/pnas.52.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Streptolysin S on Peripheral Lymphocytes of Normal Subjects and Patients With Acute Rheumatic Fever

Abstract: The human peripheral blood lymphocyte provides a readily available in vitro system, representative of the donor's immune status.1 This cell responds to specific antigens to which the donor is sensitized, as well as to certain nonspecific stimulants, such as phytohemagglutinin (PHA), an extract of the kidney bean, Phaseolus vulgaris. PHA has been used for the past 5 years as a mitogenic agent for lympho

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Streptolysin S [7,19] preparation, derived from the supernatants of resting cultures of streptococci, contain an inducer of lymphocyte transformation which ap pears to be immunologically nonspecific in its action and thus similar in action to PHA. On the other hand, streptolysin O and SK-SD prepara tions [6,7] act as specific antigens in inducing the transformation of lym phocytes of donors previously sensitized by streptococcal infection. Par ticularly, the relatively impure commercial SK-SD preparation has been frequently used in the assay of lymphocyte blastogenesis as one of the an tigens to determine the capacity of cellular immunity against streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…Streptolysin S [7,19] preparation, derived from the supernatants of resting cultures of streptococci, contain an inducer of lymphocyte transformation which ap pears to be immunologically nonspecific in its action and thus similar in action to PHA. On the other hand, streptolysin O and SK-SD prepara tions [6,7] act as specific antigens in inducing the transformation of lym phocytes of donors previously sensitized by streptococcal infection. Par ticularly, the relatively impure commercial SK-SD preparation has been frequently used in the assay of lymphocyte blastogenesis as one of the an tigens to determine the capacity of cellular immunity against streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been obtained by using streptococcal extracellular products and toxins. [21][22][23][24] Goldstein et al reported that mammalian structural glycoproteins obtained from heart valves contain antigens similar to those isolated from group A streptococcal cell walls. 25 The shared antigenicity seemed to be due to the presence of common N-acetylglucosamine terminal groups in mammalian tissue and the group A streptococcal carbohydrate.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unknown in what way mononuclear cells behave in reactions of the immediate type. It could be dem onstrated that cell transformation appears in several immunological reactions, as in mixed cultures of homologous lymphocytes, in cultures of lymphocytes from patients sensitized by tetanus and diphtheria toxoid, small pox vaccine, streptolysin S and pollenextracts (11,31,17). It needs further study to document if the morphological changes correlate in every instance with an increase of 0 2-consumption.…”
Section: Discussionmentioning
confidence: 99%